If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -3 + -6y = 0 Reorder the terms: -3 + 4y + -6y = 0 Combine like terms: 4y + -6y = -2y -3 + -2y = 0 Solving -3 + -2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2y = 0 + 3 -2y = 0 + 3 Combine like terms: 0 + 3 = 3 -2y = 3 Divide each side by '-2'. y = -1.5 Simplifying y = -1.5
| 480=48x-6x^2 | | 2x^2+2y^2+8x+12y+18=0 | | 5(4+3n)+3=98 | | (3x+5)(x+8)= | | -22=5x-x+10 | | 480=48x-.6t^2 | | -33=5(x+3)+7x | | 3x-2y+c=0 | | -11=-1-2b | | C^2=160 | | 5(x+3)+9=3(x-4)+6 | | -4y-y=-15 | | n-1.5=5.1 | | 12/18=8/y | | 6-(-1+8i)-(-7-i)= | | (10x-5y)=1 | | 2-6(r-6)=2+6(r-2) | | 4a-7=-59 | | 85+5x+10=180 | | 14=3v+5(v-2) | | 4a-7=59 | | b=1.5mv | | 9-8q+4q= | | 2q+1q= | | 75=6x+5x+9 | | 52+2x-6=180 | | -5-2n=21 | | 3(5n)+14+6n=21 | | -2(3x+6)=12 | | x(x+5)=210 | | 2X^2+-8X=0 | | 5(r-2)=-16+6r |